(untitled) (Research, Society and Development, 2021)
The working memory is a system that allows the temporary storage and manipulation of information, it is largely involved in machine learning, making decision and reasoning. Studies relate the working memory with learning and indicate improved performance through working memory training. To carry out the studies, a software (computer programs) is required to perform the working memory tasks and to provide the survey data. In this way, this study aims to perform the technological and scientific prospection of working memory tasks softwares. The scientific prospection was made by retrieving journals published in the following databases: Scopus, Web of Science, Scielo, Bireme, PubMed and Science Direct. The technological prospection was made using INPI, SpaceNet, USPTO and Web of Science databases. The search for patents on the subject did not yield results, while the search for articles resulted in 73 scientific publications, showing a deficit of article publications and patent filings, due to several factors. Therefore, the production of more scientific studies should be encouraged, as it reflects directly on the production of patents, so there are potential studies capable of directing or improving the ways of treating neurological diseases and/or psychiatric disorders, using training through working memory software.